Sporolithon aschersonii structural integrity responses across the PETM - Melbourne, Leanne; Schmidt, Daniela N; Sarkar, Suman (In: Melbourne, L et al. (2025): Assessing structural integrity responses of coralline algae across the PETM [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.978487, 2025)
This dataset contains cell measurements (length, width and wall thickness) for the coralline alga Sporolithon aschersonii. Samples were extracted from limestone collected in 2015 and 2020 in Meghalaya, NE India (Eastern Tethys), corresponding to a time before and during the Palaeocene-Eocene Thermal Maximum, PETM (~55.8 Ma).
Keywords: cell measurements; coralline algae; environmental change; PETM; resilience; structural integrity